2019
DOI: 10.23986/afsci.73282
|View full text |Cite
|
Sign up to set email alerts
|

Changes in yield and nutritive value of red clover (Trifolium pratense L.) and Festulolium (Festulolium braunii (K. Richt) A. Camus) under drought stress

Abstract: The aim of the research was to assess the impact of water stress on the yield and content of basic nutrients in the biomass of Trifolium pratense and Festulolium braunii cultivated in pure stand and in mixture. A pot experiment was carried out in 2012–2014, at two levels of soil moisture: well-watered and drought stress. The study showed that stress significantly reduced the dry matter yield (DMY), the most in T. pratense, followed by mixture, and F. braunii. The effect of drought stress on the nutritive value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Fibre promotes digestion, cleanses the digestive tract, prevents absorption of excess cholesterol [18] and aids in bowel movement by adding mass to the intestinal content [19]. Digestion of animal feed is therefore, determined by the crude fibre content [20]. Ash contents were very high in the leaves of C. aurantifolia, C. grandis, C. limon and C. paradisii, ranging from 10 to 14%.…”
Section: Discussionmentioning
confidence: 99%
“…Fibre promotes digestion, cleanses the digestive tract, prevents absorption of excess cholesterol [18] and aids in bowel movement by adding mass to the intestinal content [19]. Digestion of animal feed is therefore, determined by the crude fibre content [20]. Ash contents were very high in the leaves of C. aurantifolia, C. grandis, C. limon and C. paradisii, ranging from 10 to 14%.…”
Section: Discussionmentioning
confidence: 99%
“…Droughtinduced reductions in forage grass productivity depend on species [29] and genotype [30]. According to the latter author, drought stress significantly reduced the dry matter yield of red clover, especially when grown in a mixture with festulolium (Festulolium braunii) [31]. Kizekova et al [32] and Tucak et al [33] found high sensitivity of red clover to drought stress.…”
Section: Productivity Of Forage Grassesmentioning
confidence: 99%
“…According to Staniak [76], this hybrid under drought conditions does not respond by lowering the crude protein content of the sward. Moreover, under unfavorable environmental conditions, it favorably influences the development of other grass species more sensitive to the variability of weather conditions, which indirectly affects the protein content of the sward [76].…”
Section: The Value Of Food and Energy Of Meadow Swardmentioning
confidence: 99%